ANTIFUNGAL ACTIVITY OF CRUDE EXTRACTS OF Euphorbia tirucalli; ISOLATION AND CHARACTERIZATION OF ONE OF ITS BIOACTIVE PRINCIPLES TIRUCALLOL (FUDMA JOURNAL OF SCIENCES, 2021)
Antifungal properties of extracts from Euphorbia tirucalli against some wood decay fungi were studied. E. tirucalli fresh sample was harvested, cleansed and chipped into chips of 3 x 2 cm length and breadth. Chipped sample (846.3 g) was macerated in 1000 mL of ethyl acetate, n hexane and methanol solvents, respectively. Column chromatography experiment on E. tirucalli was carried out and antifungal screening was done according to standard method for 7 days to observe zones of inhibition of fungi growth. Broth dilution method was adopted to determine the Minimum Inhibition Concentration (MIC) and Minimum Fungicidal Concentration (MFC) of E. tirucalli extracts and fraction. Results show that Fibroporia vaillantii, Fomitopsis pinicola, Gloeophyllum sepiarium, Rhizopus sp. and Serpula lacrymans were sensitive to ethyl acetate, nâ€™ hexane and methanol E. tirucalli extracts at concentration of 200 mg/mL with zone of inhibition of  18-26 mm and  methanol extract had the highest value of 26 mm. The fraction had zone of inhibition of between 18 and 20 mm which are not significantly different (p
Keywords: Antifungal, E. tirucalli, Extract, Fraction, Wood, Fungi, Tirucallol